Análise dinâmica de uma ponte com protensão no extradorso - Fuganti, Paloma Toledo (2012)
Searching for more slender structures, economically viable and aesthetically appealing drove and innovation in the bridges. Prestressing, both internal and external, has been used on a large scale due to its efficiency; several techniques have been developed and used, as the stays. The extradosed bridge is a structure that retains characteristics of straight girder bridges built by successive balances, as well as cable-stayed bridge. Prestressing extradosed is an innovative new structure, which is not widely used in Brazil. The concept developed in 1988 was first constructed in 1994 in Japan. Because they are structures with long spans and can suffer excessive vibration when subjected to dynamic loading of high intensity such as live loads, it is important to analyze their behavior. The dynamic of structures includes determining the frequency and mode of natural vibration of the structure, as well as the possible displacements and internal forces. Computer models, using the principle of the finite element method, when properly calibrated, can represent values close to the reality of the structure in service. This paper intends to analyze the dynamic behavior of the bridge located in the TO-010, between Miracema and Lajeado, inaugurated in 2011, when subjected to different moving load, and moving at different speed, comparing them with the static analysis.